2019
DOI: 10.1002/mbo3.898
|View full text |Cite
|
Sign up to set email alerts
|

Full‐length 16S rRNA gene classification of Atlantic salmon bacteria and effects of using different 16S variable regions on community structure analysis

Abstract: Understanding fish‐microbial relationships may be of great value for fish producers as fish growth, development and welfare are influenced by the microbial community associated with the rearing systems and fish surfaces. Accurate methods to generate and analyze these microbial communities would be an important tool to help improve understanding of microbial effects in the industry. In this study, we performed taxonomic classification and determination of operational taxonomic units on Atlantic salmon microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…In other words, we confirmed that the number of different reads clustered according to the sequence similarity were fewer sFL16S method than for the V3V4 method. In a previous study, Klemetsen et al have noted that different variable regions and sequence lengths of the 16S rRNA gene will affect the microbial profile differently by taxonomic rank and phylogenetic group 25 . Therefore, we determined that the differences of sequence similarity on the 16S rRNA variable regions covered according to the read-length affected the diversity value calculation estimating their abundance.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, we confirmed that the number of different reads clustered according to the sequence similarity were fewer sFL16S method than for the V3V4 method. In a previous study, Klemetsen et al have noted that different variable regions and sequence lengths of the 16S rRNA gene will affect the microbial profile differently by taxonomic rank and phylogenetic group 25 . Therefore, we determined that the differences of sequence similarity on the 16S rRNA variable regions covered according to the read-length affected the diversity value calculation estimating their abundance.…”
Section: Resultsmentioning
confidence: 99%
“…For the full-length 16S rRNA gene sequencing, the rumen liquid samples from six dairy cows of each treatment were randomly selected. The full-length bacterial 16S rRNA genes were firstly amplified based on the genomic DNA isolated from rumen fluid using universal primers 27F (5 -AGRG TTTGATYNTGGCTCAG-3 ) and 1492R (5 -TASGGHTACCT TGTTASGACTT-3 ) with barcode in accordance with a precedent study (Klemetsen et al, 2019). All PCR reactions were performed in a 10 µL reaction containing 100 ng of extracted template DNA, 0.3 µL of each forward and reverse primers (10 µM), 2 µL of dNTP (2 mM each), 5 µL of KOD FX Neo Buf (Toyobo Co., Ltd., Osaka, Japan), and 0.2 µL of KOD FX Neo.…”
Section: Pcr Amplification and Full-length 16s Rrna Gene Sequencingmentioning
confidence: 99%
“…Henderson et al (2015) found that the microbial community and fermentation function of the rumen are predominantly shaped by the diet. It is thus significant to elucidate the effects of FSBM application in the ration of lactating dairy cows on rumen fermentation and rumen microorganisms, especially with the aid of third-generation sequencing that targets the full-length 16S rRNA gene and offers higher accuracy and resolution of microbial communities than partial 16S rRNA gene sequencing (Klemetsen et al, 2019;He et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Prepared kimchi filtrate was centrifuged (13 475 g , 5 min, 4 ℃), and the pellet obtained was washed twice with lysis buffer. DNA was extracted using a Genomic DNA preparation kit (Qiagen, Hilden, Germany) and used as a template for PCR amplification of the 16S rRNA gene using 27F and 1492R 16S universal primers (Klemetsen et al ., 2019). Purified amplicons were then used as templates for nested PCR targeting the V3 region of the 16S rRNA gene to visualise LAB in total bacterial communities using the DGGE primers of Lac1 and GC Lac2 (Lee & Lee, 2010).…”
Section: Methodsmentioning
confidence: 99%